Memoria como estrategia para incentivar el turismo en el centro histórico de Honda Tolima (2023)
The main emphasis of this project is placed on supplying the tourist deficit within the historic quarters, taking advantage of residual urban voids, more specifically, generating transformations of significant public spaces through the different ways in which memory can contribute in this type of colonial environment. starting with the participation of the community and specific urban concepts.